The civil marriage of homosexuals and the vulneration of the full respect of human rights in Perú, year 2016 - García Rivera, Francisco (2018)
The purpose of this research is to analyze the justiciary positions of justice operators in the province of Tacna regarding the violation of the fundamental human rights of persons with homosexual orientation by not being allowed to contract civil marriage in Peru in 2016. In order to meet the proposed objectives, a basic type and qualitative study was carried out. Also, the following research methods were applied: Analytical method, deductive method, comparative method, hermeneutic method, synthetic method. The investigation was carried out in the province of Tacna. The final sample consisted of 334 lawyers. In addition, various documents useful for the investigation were reviewed: Political Constitution of Peru, Jurisprudence of the Inter-American Court of Human Rights, American Convention on Human Rights, Civil Code of Peru, Peruvian Constitutional Court, Laws of countries or States where they were approved Laws granting civil marriage between persons of the same sex, Universal Declaration of Human Rights, International Charter of Human Rights, World Conference of Human Rights and the Millennium Assembly, Prevention of discrimination against human rights in the administration of justice. It was found that approximately half of the jurists surveyed assume legal positions in favor of equal or homosexual marriage in Peru. However, the majority of lawyers surveyed do not approve the legalization of gay marriage